Identification of autochthonous grapevine varieties in the germplasm collection at the ITA of Castilla y leon in Zamadueñas Station, Valladolid, Spain - Yuste, J.=700 1 Martin, J.P.; Rubio, J.A.; Hidalgo, E.; Recio, P.; Santana, J.C.; Arranz, C.; Ortiz, J.M.
(Es, En)
ilus., 14 ref.
Keywords: VID; BANCO DE GENES; MARCADORES GENETICOS; ESPAÑA; AMPELOGRAFIA; MICROSATELITES; STMS